(3GdCUhd hGdeHGOF eONd hXGFa GdeOjQs - (3aQjO agej(B, (3RjGQIs ((3YeGf(B:s (3eWHYI GdTYH(B,s, 2000)
(3efXeI GdCYeGd(B- (3JWhQ GdacQ GdEOGQj(B- (3EJNGP GdbQGQ(B- (3GdJNWjW(B- (3GdJfXje(B- (3GdbjGOI(B- (3GdQbGHI(B.s
Keywords: (3EOGQI GdCYeGds